Chapter Durumi Camp, Abuja: conflict and the spatial praxes of a furtive-periphery - Àjàdí, Stephen (Ricerche. Architettura, Pianificazione, Paesaggio, Design, 2022)
The current situation of conflict in Northern Nigeria in the past decade has been responsible for more displacement than in the region's previous recorded history. According to the Global Terrorism Index, Nigeria is the most terrorised country in Africa and the third most terrorised on the planet. The UNHCR and IDMC estimate over 3.2 million people displaced in the region with 2.58 millions of them scattered internally. The consistency of these conflicts has given rise to a perpetual process of internal displacement and rare forms of peripherality. IDP/Refugee camps are most often treated as periphery-appendices to the script of the city. As peripheries, IDP camps and informal settlements in various cities in the north are constantly faced with a pressing need to develop resilience for just surviving. There are currently no significant research attempts to study these resilience characters. The research focuses on the socio-spatial praxes of Durumi (Area 1) camp towards resilience. Durumi Camp is a rather surreptitious periphery sandwiched in a middle-class area in the city of Abuja in Nigeria. Using a mixed approach of ethnography, digital spatial analyses, and architecture, the new lives of the campers are studied in their simple but sophisticated adaptations to the dynamics of their new social and physical environment. The findings of the spatial study engage and further raise new questions and notions of the periphery in terms of socio-spatial compatibility, movement, re-enactment and re-invention of socio-spatial practices and cultures in African urbanity. The study also displaces the current theories of the periphery that describe it as fully dependent on the city center in terms of innovation. The study is a product of three years of ethnographic field work and spatial study in the area. It helps expand the discourse of the center and periphery in the context of conflict, displacement, and vulnerability.